Contribution to the knowledge of Chinese Phasmatodea V: New taxa and new nomenclatures of the subfamilies Necrosciinae (Diapheromeridae) and Lonchodinae (Phasmatidae) from the Phasmatodea of China - Ho, George Wai-Chun (Zootaxa, 2017)
This study provides descriptions of one new genus, 24 new species and four new subspecies from the Necrosciinae and Lonchodinae of China. They are, Dianphasma sparsigranulatum sp. nov., D. yui sp. nov., Micadina songxiaobini sp. nov., Necroscia dianica sp. nov., Neohirasea fenshuilingensis sp. nov., N. hujiayaoi hujiayaoi sp. nov. & subsp. nov., N. h. shengtangshanensis subsp. nov., N. nanlingensis sp. nov., N. pengzhongi sp. nov., N. unispina unispina sp. nov. & subsp. nov., N. unispina parvula subsp. nov., N. wangpengi sp. nov., Oxyartes jinpingensis sp. nov., O. rubris sp. nov., Planososibia brevialata sp. nov., P. liui sp. nov., Pseudososibia cristata gen. nov. & sp. nov., P. undulatomarginata sp. nov., Sipyloidea tuberculata sp. nov., Carausius bicornis sp. nov., C. huanglianshanensis sp. nov., C. luchunensis sp. nov., C. novus sp. nov., C. yingjiangensis sp. nov., C. yunnanensis sp. nov. and Pericentrus biwenxuani sp. nov.; suggests seven new combinations for Neohirasea asper (Redtenbacher, 1908) comb. nov. from Paramenexenus Redtenbacher, 1908, Planososibia qiongensis (Ho, 2013) comb. nov. from Sosibia Stål, 1875, Pseudososibia brachyptera (Chen & He, 2004) comb. nov. from Sosibia with the first description of the female, Phraortes albopictus (Chen & He, 2008) comb. nov. from Dixippus Stål, 1875, Lonchodes gracicercatus (Chen & He, 2008) comb. nov. from Dixippus, Lonchodes guangdongensis (Chen & He, 2008) comb. nov. from Dixippus and Lonchodes paucigranulatus (Chen & Xu, 2008) comb. nov. from Dixippus; records Pericentrus Redtenbacher, 1908 for the first time in China. Key to the species and list of the species of the studied genera including Dianphasma Chen & He, 1997, Micadina Redtenbacher, 1908, Necroscia Audinet-Serville, 1838, Neohirasea Rehn, 1904, Oxyartes Stål, 1875, Planososibia Seow-Choen, 2016, Pseudososibia gen. nov., Sipyloidea Brunner von Wattenwyl, 1893 and Carausius Stål, 1875 are provided.